Aplikasi Pemetaan Kantor Unit Pelaksana Teknis Daerah (UPTD) Pengelolaan Sampah Kabupaten Tangerang Berbasis Mobile - Moorent, Muhammad Rob; Anwar, Nizirwan; Widodo, Agung Mulyo; Sekti, Binastya Anggara (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
The Environmental and Hygiene Department is responsible for the management of garbage in the district of Tangerang. Further, the 2020 population census shows that, by September 2020, thepopulation of Tangerang District had reached 3.25 million people. This figure is comparable to the estimated population based on the data of Adminduk Ditjen Dukcapil in December 2020, which was3.06 million people. With the population in the largest district or city in Indonesia, according to theCentral Statistics Authority, As demonstrated by the population data for 2020, there are a lot ofWaste Management Place in Tangerang. The purpose of this application is to increase publicknowledge about the information and facilities of the UPTD Section of Waste Management due tothe public's lack of knowledge about Waste management sites. To make the operation of applicationseasier, the Dart programming language is combined with Framework Flutter and the utilities usedin the creation of this information system model using the UML modeling method.